2001
DOI: 10.1002/jbm.1226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low‐intensity pulsed ultrasound on proliferation and chondroitin sulfate synthesis of cultured chondrocytes embedded in Atelocollagen® gel

Abstract: The effects of low-intensity pulsed ultrasound (US) on the proliferation and chondroitin sulfate synthesis of cultured chondrocytes embedded in Atelocollagen gel in vitro were examined. Articular cartilage was harvested from the hip, knee, and shoulder joints of 10-week-old Japanese white rabbits. Chondrocytes isolated by collagenase digestion were embedded in type I collagen gel, Atelocollagen gel, and were cultured in Dulbecco's modified eagle's medium for 3 weeks. The US apparatus, SAFHS, was used to delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 33 publications
(41 reference statements)
1
49
1
Order By: Relevance
“…The LIUS treatment was shown to have an effect on the proliferation of fibroblsts, osteoblast, and monocyte (28,31), but not in chondrocytes both in 3-D and monolayer cultures (18,19). In our experiment, however, the pretreatment of LIUS reduced the time to population doubling of the replated cells in monolayer culture until passage 2, when compared to the untreated control (Table 2).…”
Section: Sox-9contrasting
confidence: 50%
See 1 more Smart Citation
“…The LIUS treatment was shown to have an effect on the proliferation of fibroblsts, osteoblast, and monocyte (28,31), but not in chondrocytes both in 3-D and monolayer cultures (18,19). In our experiment, however, the pretreatment of LIUS reduced the time to population doubling of the replated cells in monolayer culture until passage 2, when compared to the untreated control (Table 2).…”
Section: Sox-9contrasting
confidence: 50%
“…LIUS is also reported to enhance repair of articular cartilage in animal model of cartilage defect (16,17). In cultured chondrocytes in vitro, LIUS stimulation enhances the synthesis of matrix proteins such as collagen type II and proteoglycans depending on the culture condition and LIUS intensity (18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Similarly, the LIUS treatment at low intensities (50 to 120 mW/cm 2 ) did not stimulate chondrocyte proliferation in studies using a monolayer culture (12), and in atelocollagen gel culture (27). On the contrary, Huang et al found that the total cell density in osteoarthritic rat cartilage was increased after LIUS treatment as compared with the control group (11,27). Therefore, the effects of LIUS on chondrocyte proliferation are still controversial, depending on the experimental systems applied.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, we selected randomly the non-affected area of human OA cartilages for explant cultures and found no significant changes in chondrocyte proliferation by various the intensity of LIUS. Similarly, the LIUS treatment at low intensities (50 to 120 mW/cm 2 ) did not stimulate chondrocyte proliferation in studies using a monolayer culture (12), and in atelocollagen gel culture (27). On the contrary, Huang et al found that the total cell density in osteoarthritic rat cartilage was increased after LIUS treatment as compared with the control group (11,27).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation